Carbonized polyaniline bridging nanodiamond-graphene hybrids for enhanced microwave absorptions with ultrathin thickness. (17th July 2020) - Chen, Xiangnan; Xu, Hairui; Zhang, Yan; Tao, Lei; Yuan, Lufeng; Meng, Fanchen; Huang, Ruoxuan; Wang, Pei; Zhou, Zuowan
Abstract: For conventional design of the electromagnetic absorption materials, introduction of magnetic materials into dielectric materials has been found to achieve better impedance matching, but lead to increase in weight and decrease in chemical stability, therefore limiting their practical applications. In this work, metal-free electromagnetic coupling was achieved by the design of nitrogen-doped nanodiamond/graphene hybrids. Polyaniline is used to self-assembled bridge the nanodiamond and graphene, and the carbonization is carried out for construction and regulation of the CN polarization and nitrogen doping. The carbonized hybrid exhibits remarkably enhanced broadband electromagnetic absorption with the optimal reflection loss value around −47.7 dB at 13.8 GHz with an ultrathin thickness of 1.8 mm. The enhancement in electromagnetic absorption is confirmed to result from nitrogen doped ND induced magnetic dissipation and the CN multi-polarization modes, as well as the multiple interfacial structures. This work opens a new route realizing lightweight electromagnetic absorption through constructing nitrogen doped carbon nanomaterial.